Resource allocation in the cotton textile industry - Dharma Kumar; Nag, S. P.; Venkataramanan, Lalgudi S.; Institute of Economic Growth, Delhi (London : Asia Pub. House, 1965)
Contains research studies on different aspects of the Indian textile industries focusing on the impact industrialization on exports of the minerals from India. Contents include: import substitution in the Indian textile industry, by Dharma Kumar; Factors determining utilization of installed capacity in the textile industry in India, by S.P. Nag; Hedging stocks and future contract in India cotton industry, by L.S. Venkataramanan.
Include bibliographical footnotes and index.
kjo 16/01/2019
Loans
Keywords: Cotton trade; Textiles industry; Cotton manufacture